Recurrence of a Pancreatic Cystic Lymphangioma After Diagnosis and Complete Drainage by Endoscopic Ultrasound with Fine-Needle Aspiration - Mansour, Nabil M; Salyers Jr, William J (JOP. Journal of the Pancreas, 2013)
Context Lymphangiomas are uncommon benign neoplasms that result from a blockage of the lymphatic system. Pancreatic cystic lymphangiomas are extremely rare. Pancreatic cystic lymphangiomas have been classically diagnosed on histopathologic examination following surgical excision, but recent reports have demonstrated successful diagnosis using endoscopic ultrasound with fine-needle aspiration (EUS-FNA). Data on the natural history of these lesions following drainage via EUS-FNA are lacking. We present a case of successful initial diagnosis and drainage of a pancreatic cystic lymphangioma using EUS-FNA, with unfortunate recurrence of the lesion four months later. Case report A 50-year-old female was evaluated for epigastric abdominal pain and nausea. CT scan revealed a 4 cm retroperitoneal cystic lesion. EUS-FNA was performed with complete drainage of the lesion using a 22-gauge needle. Twenty-five mL of chylous white fluid was obtained with laboratory analysis consistent with a pancreatic cystic lymphangioma. The patient was symptom-free for 4 months following drainage, but eventually had symptoms again with a CT scan confirming recurrence. Conclusions While EUS-FNA is effective for the diagnosis of pancreatic cystic lymphangiomas, its role in the management of these lesions is questionable. Temporary relief of symptoms can be achieved after EUS-guided drainage, but recurrence is a concern. Definitive cure likely requires complete surgical excision. Image: White, chylous fluid aspirated from cystic lesion.